UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE COOPERATIVE SCRIPT PADA SISWA KELAS VIIIA SMP N 1 BINANGUN CILACAP - Ruminah Ruminah; AA Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
Cooperative script method is one method to improve student’s interest in learning and students' achievement. This research is Classroom Action Research (CAR). The subject of the research is eight grade students of Junior high school Binangun Cilacap. It is conducted in two cycles, each cycles consists of planning, acting, observing and reflecting. The data revealed from observation, questionnaire, test and documentation. The result of the research was there are increasing student interest and students' achievement. This forum can be teachers' reflection to be much better in mathematic teaching and learning.